THE EFFECT OF WALKING EXERCISE PROGRAM (WEP) TO DECREASE CANCER RELATED FATIGUE (CRF) IN CHILDREN WITH LEUKEMIA - Dini Maulinda; Angga Arfina; Eka Malfasari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
Cancer Related Fatigue (CRF) in children with leukemia is one of the complaints that is often experienced due to the effects of chemotherapy. One of the actions that can be done to reduce it is through the Walking Exercise Program (WEP). WEP is a program exercise developed based on the principles of frequency, duration, intensity, and activity. The purpose of this study was to determine the effect of physical exercise WEP on fatigue in children with leukemia with the design